Measuring and interpreting platelet-leukocyte aggregates. (3rd October 2018) - Finsterbusch, Michaela; Schrottmaier, Waltraud C.; Kral-Pointner, Julia B.; Salzmann, Manuel; Assinger, Alice
Abstract: Platelets, besides their specialised role in haemostasis and atherothrombosis, actively modulate innate and adaptive immune responses with crucial roles in immune surveillance, inflammation and host defence during infection. An important prerequisite for platelet-mediated changes of immune functions involves direct engagement with different types of leukocytes. Indeed, increased platelet-leukocyte aggregates (PLAs) within the circulation and/or locally at the site of inflammation represent markers of many thrombo-inflammatory diseases, such as cardiovascular diseases, acute lung injury, renal and cerebral inflammation. Therefore, measurement of PLAs could provide an attractive and easily accessible prognostic and/or diagnostic tool for many diseases. To measure PLAs in different (patho-)physiological settings in human and animal models flow cytometric and microscopic approaches have been applied. These techniques represent complementary tools to study different aspects relating to the involvement of leukocyte subtypes and molecules, as well as location of PLAs within tissues, dynamics of their interactions and/or dynamic changes in leukocyte and platelet behaviour. This review summarises various approaches to measure and interpret PLAs and discusses potential experimental factors influencing platelet binding to leukocytes. Furthermore, we summarise insights gained from studies regarding the underlying mechanism of platelet-leukocyte interactions and discuss implications of these interactions in health and disease.